FeS2 nanoparticles on reduced graphene oxide: an efficient electrocatalyst for nitrate electroreduction to ammonia. Issue 44 (7th November 2022) - Zhang, Nana; Zhang, Guike; Tian, Ye; Tang, Yanxia; Chu, Ke
Abstract : FeS2 /RGO has been demonstrated as an efficient and durable catalyst for electrocatalytic nitrate-to-ammonia conversion (NO3 RR), attributed to the efficient activation of NO3 − on surface Fe sites to energetically facilitate the NO3 RR process. Abstract : Electrocatalytic nitrate-to-ammonia conversion (NO3 RR) represents a promising approach for achieving both sustainable NH3 synthesis and wastewater treatment. Herein, we first demonstrate the great feasibility of using pyrite FeS2 as an effective and durable NO3 RR catalyst. The developed FeS2 nanoparticles supported on reduced graphene oxide (FeS2 /RGO) deliver the maximum NH3 -Faradaic efficiency of 83.7% with a corresponding NH3 yield of 2.32 mg h −1 cm −2 at −0.6 V (RHE). FeS2 /RGO also exhibits excellent stability during the cycling and long-term electrolysis tests. DFT calculations reveal that NO3 − can be efficiently activated on surface Fe sites, which can drive the NO3 RR process through an NHO pathway with a low energy barrier.